Thermal quenching mechanism of photoluminescence in 1.55 mu m GaInNAsSb/Ga(N)As quantum-well structures - Sun, Handong (2009)
The authors report the temperature dependent photoluminescence characteristics of a series of GaInNAsSb/Ga(N)As double quantum wells which all emit at 1.5-1.55 mu m at room temperature and whose design is such that the quantum wells have nominally identical valence band profiles but show different confinement depth in the conduction band. The photoluminescence quenching at high temperature demonstrates a thermal activation energy independent of the conduction band offset and can be most plausibly attributed to the unipolar thermalization of holes from the quantum wells to the barriers. This effect will intrinsically limit the flexibility of heterostructure design using GaInNAs(Sb), as it would for any other material system with small valence band offset. (c) 2006 American Institute of Physics.